FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI 3 TPMB WILAYAH KERJA PUSKESMAS WALUYA TAHUN 2023 - Suryani, Fauziah; Musmundiroh, Musmundiroh (NHM PRESS, 2024)
ABSTRACT Hyperemesis gravidarum is a symptom of continuous vomiting more than 10 times, eating too little, causing disruption to the atmosphere of daily life and can cause dehydration. In Indonesia, there are 50-75% of cases of nausea and vomiting experienced by pregnant women in the first trimester or early pregnancy, while 13% of pregnant women experience nausea and vomiting in West Java. This study aims to determine the factors that influence hyperemesis gravidarum in pregnant women in the 1st trimester in the TPMB of the Waluya Public Health Center Work Area in 2023. This type of research is a quantitative analytical study. The design used is cross sectional. Where the independent variables are (age, parity, occupation, education and knowledge) while the dependent variable is (hyperemesis gavidarum). The population in this study was 453 pregnant women in the first trimester who underwent ANC in 3 TPMBs in the Waluya Health Center Working Area for the period January-June 2023. The sample in this study used the Slovin formula to obtain 81 samples using a random sampling technique. The instrument used was a questionnaire in the form of a Google form. Data were analyzed using the chi-square test. The results show that the variables that influence hyperemesis gravidarum in the 3 TPMB of the Waluya Health Center Working Area in 2023 are age (p=0.001), parity (p=0.025), occupation (p=0.027), education (p=0.675), and knowledge (p =0.021). Of these 5 variables, there are 4 variables that are interconnected, while 1 other variable, namely education, has no relationship with the incidence of hyperemesis gravidarum. It is hoped that respondents who experience hyperemesis gravidarum will be able to understand the impact of excessive nausea and vomiting, if not treated properly it can threaten the mother and baby.